Essential MATLAB for engineers and scientists - Hahn, Brian D.; Valentine, D. T. (Butterworth Heinemann, 2007)
The essential guide to MATLAB as a problem solving toolThis text presents MATLAB both as a mathematical tool and a programming language, giving a concise and easy to master introduction to its potential and power. Stressing the importance of a structured approach to problem solving, the text gives a step-by-step method for program design and algorithm development. The fundamentals of MATLAB are illustrated throughout with many examples from a wide range of familiar scientific and engineering areas, as well as from everyday life.Features:. Includes MATLAB Version 7.2, Release 2006a. Numerous simple exercises provide hands-on learning of MATLAB's functions. A new chapter on dynamical systems shows how a structured approach is used to solve more complex problems.. Common errors and pitfalls highlighted. Concise introduction to useful topics for solving problems in later engineering and science courses: vectors as arrays, arrays of characters, GUIs, advanced graphics, simulation and numerical methods. Text and graphics in four colour. Extensive instructor supportEssential MATLAB for Engineers and Scientists is an ideal textbook for a first course on MATLAB or an engineering problem solving course using MATLAB, as well as a self-learning tutorial for students and professionals expected to learn and apply MATLAB for themselves.Additional material is available for lecturers only at http://textbooks.elsevier.com . This website provides lecturers with:A series of Powerpoint presentations to assist lecture preparationExtra quiz questions and problemsAdditional topic materialM-files for the exercises and examples in the text (also available to students at the book's companion site )Solutions to exercisesAn interview with the revising author, Daniel Valentine · Numerous simple exercises give hands-on learning· A chapter on algorithm development and program design · Common errors and pitfalls highlighted· Concise introduction to useful topics for solving problems in later engineering and science courses: vectors as arrays, arrays of characters, GUIs, advanced graphics, simulation and numerical methods· A new chapter on dynamical systems shows how a structured approach is used to solve more complex problems.· Text and graphics in four colour· Extensive teacher support on http://textbooks.elsevier.com: solutions manual, extra problems, multiple choice questions, PowerPoint slides· Companion website for students providing M-files used within the book